The price of sexual services in nightclubs and massage parlors of San José, Costa Rica: biological and anthropological interpretations - Mónge-Nájera, Julián (2011)
Humans and other primates exchange sex for resources. In the case of humans, this exchange includes sexual work. There are few previous studies on sex work in San José, Costa Rica that include data on how much is paid for sexual services. We studied the price of female sex work, and how the profits are distributed among all parties, in nightclubs and massage parlors, by obtaining data from interviews with workers and owners, and from telephone calls, from 1994 through 2010. Prices ranged from US$6 for a lap dance to US$300 for intercourse and when inflation is taken into account, they have not increased much in the last ten years. The prices per hour can reach 125 times the minimal wage per hour of work in the country. In comparison with independent sex work done in the streets, parlor and club women benefit from the associated infrastructure, access to clients, and safety, and they receive 40-50 % of the fee paid by men for their direct services (dances, sexual activity), so there is no indication of exploitation on either side. Nightclubs have around 30% of profit after expenses are deduced. Sexual services are relatively expensive but men pay them because they are biologically and socially oriented towards wanting these services.